Native protest outside Reed Paper art show - Vancouver Art Gallery - Pacific Tribune (photographer) (1977)
Demonstrators outside Vancouver Art Gallery show sponsored by Reed Paper draw attention to company's mercury pollution of water in northern Ontario that caused degenerative disease among local First Nations living on the waterway.